An analysis of the welfare of fast-growing and slower-growing strains of broiler chicken - Nicol, Christine Janet; Abeyesinghe, Siobhan Maya; Chang, Yu-Mei (Frontiers in Animal Science, 2024)
Due to concerns about the welfare of fast-growing (FG) strains of broiler chicken, animal welfare organisations have advocated the use of certain slower-growing (SG) strains that meet key welfare targets under test conditions. However, a widespread transition to SG strains could negatively affect sustainability because these birds tend to have higher feed conversion ratios and longer production cycles. It is important therefore to review the extent and limits of SG welfare improvements under test conditions and on commercial farms, to support the best policy decisions. Following a systematic literature search, 63 source papers were identified. Most reported comparative welfare outcomes for at least one SG strain with at least one FG counterpart, whilst a minority examined the suitability of various SG strains for niche production. The literature review considered different types of study design and accounted for confounding factors such rearing environment and diet. Additionally, a quantitative analysis of effect size for mortality, gait score and contact dermatitis was conducted across studies that had compared birds under similar rearing conditions and that had used SG strains with an average daily growth rate of at least 40g/day. Modern, commercial SG strains performed better on most relevant welfare traits than FG strains. This was the case even when the 'fairest' comparisons were made at equivalent bodyweights (when SG birds were older), under matched-environmental conditions, experimentally or on farm. The quantitative analysis found that FG strains had a higher estimated incidence rate ratio for mortality (risk of death over a given period of time) of between 1.69 and 2.16, contact dermatitis affecting 15-25% more birds, and a mean gait score 0.65 points higher than SG strains. FG strains were also less active but other differences in behaviour were inconsistent with some behaviours (e.g. dustbathing) often absent altogether. Growth rate was generally, but not always, predictive of welfare problems. Alternative strategies, such as the slaughter of birds prior to the onset of any welfare decline, could be evaluated in future in terms of welfare improvement and efficiency of production.